SUBJECTIVE WELL-BEING OF ADOLESCENTS WITH PARENTS AS INDONESIAN MIGRANT WORKERS IN DAREK PRAYA VILLAGE, CENTRAL LOMBOK - MAULIDA JUNIAR SHAHARA; SARAPUDIN (Universitas Islam Negeri Mataram, 2023)
In children of migrant workers, they will face a number of developments without the complete presence of their parents, even though they need guidance, support and supervision from their parents so that these adolescents will feel a lack of happiness and satisfaction with their lives such as low subjective well-being. This study uses a qualitative approach, which aims to find out (1) How is the dynamics of subjective well-being in adolescents with parents as Indonesian migrant workers in Darek Village. And (2) how is the subjective well-being strategy carried out by adolescents with their parents as migrant workers in Darek Village. The data collection techniques in this study used interview, observation and documentation techniques with adolescents whose parents lived as migrant workers, adolescents aged 10-19 years and people who lived with the subject, as the primary data source. The results of this study indicate that: (1) ) The dynamics of subjective well-being in adolescents with parents as migrant workers in Darek Village, Praya District, Central Lombok Regency include self-acceptance, positive relations with others, autonomy, environmental mastery, goals in life and personal growth and includes elements of subjective well-being Affective and Cognitive. (2) The subjective welfare strategy carried out by adolescents with parents as migrant workers in Darek Village, Praya District, Central Lombok Regency can change negative affection into positive effects so as to get life satisfaction.